2014
DOI: 10.1088/1742-6596/502/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Water-enhanced Adhesion at Interface in Immiscible Bilayer Film of Polystyrene and Poly(methyl methacrylate)

Abstract: Abstract. From nano-scratch tests, strong interfacial adhesion has been found for polystyrene (PS) and poly(methyl methacrylate) (PMMA) bilayer films prepared by a water floating (WF) method, while a PS layer on a PMMA film produced by a spin coating (SC) method peels off easily at the interface. Neutron reflectivity measurements demonstrated a clear difference in the interfacial width (σ) between the two bilayers; σ = 9 nm for the film obtained by the WF method, whereas σ = 5 nm for that by the SC method. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Among them are Lorenzoni et al who studied the nanomechanical properties of solvent cast polymer thin polystyrene (PS) and poly(methyl methacrylate) (PMMA) blends and PS‐ b ‐PMMA block copolymers. Using the nanoscratching procedure Harada et al found a strong interfacial adhesion for PS and PMMA bilayer films prepared using water floating technique, while a PS layer on a PMMA film was produced via spin coating method which peels of easily at the interface . The nanomechanical properties of PS‐ b ‐PMMA copolymers combined with reduced graphene oxide sheets (RGO) were analyzed using Berkovich nanoindentation .…”
Section: Introductionmentioning
confidence: 99%
“…Among them are Lorenzoni et al who studied the nanomechanical properties of solvent cast polymer thin polystyrene (PS) and poly(methyl methacrylate) (PMMA) blends and PS‐ b ‐PMMA block copolymers. Using the nanoscratching procedure Harada et al found a strong interfacial adhesion for PS and PMMA bilayer films prepared using water floating technique, while a PS layer on a PMMA film was produced via spin coating method which peels of easily at the interface . The nanomechanical properties of PS‐ b ‐PMMA copolymers combined with reduced graphene oxide sheets (RGO) were analyzed using Berkovich nanoindentation .…”
Section: Introductionmentioning
confidence: 99%